Disclosure of the Potential of Bitumen Emulsion in Waterproofing and Roofing Works - Nurbek Sharibaev; Sobir Sharipbaev; Sherzod Djuraev; Nosir Sharibaev (Genius Journals, 2023)
Bitumen emulsion has significant potential in waterproofing and roofing applications due to its unique properties and versatility. This article aims to explore and disclose the potential of bitumen emulsion in these specific works. It highlights the advantages of using bitumen emulsion for waterproofing and roofing, including its excellent adhesion, flexibility, and ability to form a seamless barrier. Additionally, the article discusses various techniques and methods of application, such as spray, brush, or trowel, that can be employed in waterproofing and roofing projects. Furthermore, the environmental benefits of using bitumen emulsion, such as low VOC emissions and reduced energy consumption, are also highlighted. By harnessing the potential of bitumen emulsion, waterproofing and roofing works can benefit from a durable and reliable solution that ensures long-lasting protection against water infiltration and enhances the overall performance of structures.
Keywords: Bitumen emulsion; waterproofing; roofing